Sustainable finance as a new financial investment model - Dziawgo, Danuta (Zrównoważone finanse jako nowy model dla inwestycji finansowych, 2019)
The subject of this study are legal regulations and guidelines concerning sustainable finance. The research objective is to identify the need of reshaping the process of financial assets under management. The object of the research is the overlapping processes on the financial markets between general investment based on financial efficiency and investment concerning social responsibility. The following research methods were used in the development of this article: the analysis of the literature of the subject, analysis of legal acts, desk research, observations, descriptive and comparative analysis. The main conclusion is that the current process of optionally including ESG criteria (environmental-social-governance) during investment decisions is being substituted by obligatory requirements in legal acts. As a result, the modest evolution of financial markets with regard to ESG consideration has accelerated significantly. It is to be expected that assets that also consider non-financial preferences will dominate financial markets in the future. This ongoing trend may be considered as a significant revolution in investment
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 23-34